2022
DOI: 10.3390/jcm11133648
|View full text |Cite
|
Sign up to set email alerts
|

Does an Adjustable-Loop Device Loosen following ACL Reconstruction with a Hamstring Graft? A Retrospective Study with a Follow-Up of Two Years

Abstract: Arthroscopic anatomic anterior cruciate ligament reconstruction (ACLR) is the gold standard treatment for an ACL tear and requires the use of fixed or adjustable-loop devices to fix a femoral-side graft. Although the adjustable mechanism is designed to provide one-way tensioning, there is a concern that the adjustable loop will loosen and lengthen during cyclic loads, creating graft laxity. The present paper is a retrospective study of patients who underwent ACLR with the fixation of a hamstring graft with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“… 5 Furthermore, retrospective studies have found noninferiority of ALB graft fixation in comparison with CLB. 13 , 27 , 39 A systematic review and meta-analysis concluded that the scarce evidence suggests no difference in knee stability and subjective knee function between ALB and CLB. 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Furthermore, retrospective studies have found noninferiority of ALB graft fixation in comparison with CLB. 13 , 27 , 39 A systematic review and meta-analysis concluded that the scarce evidence suggests no difference in knee stability and subjective knee function between ALB and CLB. 14 …”
Section: Discussionmentioning
confidence: 99%
“…5 Furthermore, retrospective studies have found noninferiority of ALB graft fixation in comparison with CLB. 13,27,39 A systematic review and meta-analysis concluded that the scarce evidence suggests no difference in knee stability and subjective knee function between ALB and CLB. 14 In previous generations of ALB, different approaches were presented to prevent slippage of the constructs and to improve primary stability.…”
Section: Discussionmentioning
confidence: 99%
“…Their loop can be tightened and adjusted according to the tunnel length during the surgical process, thereby decreasing the possibility of a bungee cord effect 14 . Although the adjustable mechanism is superior in design, some studies have pointed out that the loop will loosen and lengthen during cyclic loads, creating graft laxity 15 . Furthermore, biomechanical studies have shown a considerable amount of loosening in adjustable‐loop devices, which might affect clinical results after ACLR 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“… 14 Although the adjustable mechanism is superior in design, some studies have pointed out that the loop will loosen and lengthen during cyclic loads, creating graft laxity. 15 Furthermore, biomechanical studies have shown a considerable amount of loosening in adjustable‐loop devices, which might affect clinical results after ACLR. 16 , 17 The application of a bioabsorbable interference screw allows the graft to be strongly fixed at the level of the joint line, which will help minimize BTE.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, adjustable-loop devices are the newer version of femoral cortical suspension devices, as they are simple to use, provide excellent results, and offer multiple advantages. One of the most commonly used devices is the titanium adjustable loop button that was used for soft-tissue fixation to the bone since titanium is thought to be the most biocompatible metal, due to its bio-inertness, corrosion resistance, high fatigue limit, and capacity for osseointegration [ 11 , 12 , 13 ]. Polyetheretherketone (PEEK) materials are stable and biocompatible and are utilized in orthopedic surgery [ 14 ].…”
Section: Introductionmentioning
confidence: 99%